Mechanism of differential sensitivity of human bladder cancer cells to mitomycin C and its analogue. - Xu, B. H. (1994)
This study was undertaken to elucidate the mechanism(s) of differential sensitivity of human bladder cancer cell lines J82 and SCaBER to mitomycin C (MMC) and its analogue, BMY 25067. The IC50 values for MMC and BMY 25067 in the SCaBER cell line were respectively 5- and 4-fold higher than in J82. BMY 25282 and BMY 25067 were significantly more cytotoxic, on a molar basis, than MMC in both the cell lines. NADPH cytochrome P450 reductase and DT diaphorase activities were significantly higher in the J82 cell line than in SCaBER, suggesting that relatively lower sensitivity of the SCaBER cell line to MMC and BMY 25067 may be due to deficient drug activation. This conclusion was supported by the observation that IC50 values for BMY 25282, which has lower quinone reduction potential than MMC and BMY 25067, did not differ significantly in these cell lines. A correlation between drug sensitivity, oxyradical formation and levels of antioxidative enzymes was not observed. These results suggest that the relatively lower sensitivity of SCaBER cells to MMC or BMY 25067 may be independent of differential oxyradical formation. MMC-induced DNA interstrand cross-link (ISC) formation was markedly lower in the SCaBER cell line than in J82. However, it remains to be seen if the reduced ISC frequency in the SCaBER cell line is a consequence of deficient drug activation or results from increased repair of the damaged DNA.